2004
DOI: 10.1007/bf02344706
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of gingival crevicular fluid for estimation of blood glucose level

Abstract: Development of a non-invasive method for measuring the blood glucose level is an urgent necessity, and putting such a method into practical use will enable some of the physical and mental stress that patients with diabetes have to endure to be removed. To realise a non-invasive blood glucose monitor, the gingival crevicular fluid (GCF) was measured. A GCF-collecting device was developed that was designed to be disposable, biocompatible and small enough to be inserted in the gingival crevice for collection of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
(10 reference statements)
2
18
0
Order By: Relevance
“…The correlation coefficient was lower than the one Parker reported as 0.975 (1993). However, it was almost the same result as the correlation coefficient, between 0.705 and 0.877, that the authors indicated for healthy subjects (Yamaguchi et al, 2004). The diabetes period was not considered to influence the GCF glucose level with regards to the subject with the diabetes period for 4.8 ±1.7 yr (mean ± SD).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…The correlation coefficient was lower than the one Parker reported as 0.975 (1993). However, it was almost the same result as the correlation coefficient, between 0.705 and 0.877, that the authors indicated for healthy subjects (Yamaguchi et al, 2004). The diabetes period was not considered to influence the GCF glucose level with regards to the subject with the diabetes period for 4.8 ±1.7 yr (mean ± SD).…”
Section: Resultssupporting
confidence: 54%
“…The use of GCF-collecting device with a testing tape saturated with enzyme as a collecting tape, simultaneous analysis of GCF could be possible (Yamaguchi et al, 2001(Yamaguchi et al, , 2002a(Yamaguchi et al, , 2002b(Yamaguchi et al, , 2004. In addition, not only the use of the non-invasive blood glucose level measurement via GCF, but also the application to qualitative and quantitative analyses for various diseases will be the subject of further study.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The gingival crevice contains a robust microbial population that is consistently bathed in crevicular fluid, which differentiates it from the tooth surface, which is immersed in saliva. Crevicular fluid is a plasma exudate that passes through the gingiva and flows along the teeth (20) and contains a number of potential carbon sources including sugars, small acids, and amino acids (6,11,20,48). A. actinomycetemcomitans primarily resides in the "moderate" pockets (4 to 6 mm in depth) in the gingival crevice instead of the deeper portions (9).…”
mentioning
confidence: 99%